Comparing Occupational Health And Safety (OHS) Management Efforts And Performance Of Nigerian Construction Contractors - Idoro, Godwin Iroroakpo (Penerbit Universiti Sains Malaysia, 2011)
The study compares the management efforts and performance of construction contractors in Nigeria with regard to Occupational Health and Safety (OHS). The purpose of the study is to help all categories of construction contractors in Nigeria to improve their management efforts related to OHS. Toward this end, a feld survey was conducted with a sample of forty contractors selected via purposive sampling. The scope of operations of the contractors was designated as multinational, national, regional or local. Six OHS management parameters and seven OHS performance parameters were used, and data were collected using structured questionnaires and analysed using mean and analysis of variance. The results reveal that contractors’ OHS-related management efforts are not correlated with the scope of their operations. The OHS performance of the contractors remains the same in terms of six performance indicators but differs in terms of the rate of accidents per worker. The study results also reveal that the accident and injury rates in the Nigerian construction industry are high. Thus, the results reveal the challenges facing Nigerian contractors and other stakeholders working to improve the OHS performance of the industry. The fndings indicate the need for effective risk management and regulation and control of OHS in the Nigerian construction industry.